Labor market rigidity and the success of economic reforms across more than one hundred countries - Forteza, Alvaro (Policy research working papers / World Bank, 2001)
Labor market policies and institutions affect the success of economic reform but probably more for political than for economic reasons. Growth appears not to be hurt by minimum wages and mandatory benefits. But the relative size of organized labor (in government and elsewhere) is crucial.